You are on page 1of 43

# 5.

3 INVERSE FUNCTION

1
INVERSE FUNCTION

## If f :x y is a function that maps x to y,

then the inverse function is denoted by f 1
where f 1 is a function that maps y back to x.

x y
Note :

f 1 1
f-1 
f (x2)
Suppose,

## f (x) = y then f-1(y) = x

Df = Rf-1

Rf = Df-1

3
An inverse function of f exists only if the
function f is a ‘ one to one ‘ function.

## Method to test wether a function is 1-1 :

i. Algebraic approach.
- if f ( x1 ) = f ( x2 ) ,
then x1 = x2

4
ii) Horizontal line test ( graphical approach)

##  If the horizontal line intersects the

graph of the function only once , then
the function is one – to- one.

a) b)

The
The horizontal
horizontal line
line
intersects
intersects
one-to-one the graph Not
at one one-to-one
point.
the graph at two points. 5
ii) Horizontal line test ( graphical approach)

##  If the horizontal line intersects the

graph of the function only once , then
the function is one – to- one.

a) b)

The
The horizontal
horizontal line
line
intersects
intersects
one-to-one the graph Not
at one one-to-one
point.
the graph at two points. 6
Method Of Finding The Inverse Function

## 1) Using Formula f [ f -1(x) ] = x

2) By substitution

Note :
i) (f-1)-1 = f
ii) f-1(f(x)) = x and f(f-1(x)) = x
iii) (fg)-1 = g-1  f-1
7
Example 1 :

## The function g is defined by

g : x  (x  1) 2  2 , x  R

## Explain why g has no inverse.

If the domain of g is x  R , x  0 ,
find g -1 and sketch the graph of g
and g-1. State the domain and range of g-1.

8
By Horizontal Line Test ,
y

y = ( x + 1)2 - 2

y = k

x
Min point Graph y = k intersects
y = (x+1)2 - 2 at two points
(-1, -2)
It is seen that g(x) is not one – to – one.
Hence, g has no inverse 9
To find g-1 ,
Let y = ( x + 1)2 - 2
y + 2 = ( x + 1)2
x + 1 =  y2
( taking the + sign
x = y2 - 1 because x  0 )

That is g-1 ( y ) = y  2 1

Let y = x
Hence,
g1(x)  x  2  1 10
y

y = ( x + 1)2 – 2 , x  0
y

x
Min point
(-1, -2)
11
If the domain of g is x  R , x  0 ,
then g is one – to one - and hence
g -1 exists .
y
y=k
g
g-1

-1 x
-1

Dg = [0,) , Rg =[-1, )

D  [-1, ) , R  [0, ) 12
g1 g1
Example 2 :

4
Given f(x) = x  3 . Find f-1(x)

Solution :
f[f 1(x)]  x
4
x
f 1(x)  3
xf 1(x)  3x  4

1 4  3x
 f (x ) 
x 13
Example 3 :
Find the inverse for each of the following
function :

a) f(x)  2x  1, xεR
3
b) f (x)  2x  1, xεR
3 2
c) f (x)  x  , xεR
3
x 1
d) f (x)  , x  2
x2

14
Solution :
a) f(x)  2x  1, xεR
f[f 1(x)]  x
2f 1(x)  1  x
1 x 1
 f (x ) 
2
3
b) f (x)  2x  1, xεR
2(f 1(x))3  1  x
1 x 1
f (x )  3
2 15
3 2
c) f (x)  x  , xεR
3
1
f[f (x)]  x
Let f 1(x)  y
f(y )  x
3 2
y  x
3
2
y  x
3
3
1 2
 f (x)  3 x 
3 16
Example 4 :
Given that f (x) = 3x + 5. Find
(a) (f –1 )2
(b) (f 2)-1

17
Solution :
(a) (f-1) 2

y 5  x 5
 f 1
x= 
3  3 
x 5 x 5
f -1(x)= 5
3  3
3
x  20

9 18
(b) (f 2) -1

## f 2(x) = f [f (x)] Let w = 9x + 20

= f(3x + 5)
x = w  20
= 3(3x + 5) +5
9
= 9x + 20
x  20
f 
2 1
x  
9

•Note that : f   f 
1 2 2 1

19
Example 5 :
The functions f and g are defined by
f : x  2x + 3 and g : x  x – 1. Find

a) f -1 and g -1
1 1
b) g  f and f  g
c)  f  g
1

1 1
d) g  f

20
Solution :
a) f : x  2x + 3 g : x  x – 1.

## Let y = 2x + 3 Let w =x–1

x = y 3 x = w + 1
2
that is that is
y 3
f y 
1 g-1(w) = w + 1
2
or x 3 or
f x  
1

2 g-1(x) = x + 1
21
1 1
b) g f f g

g  f x
1
 gf x
1

f  g 
1
x  f 
g 1
x 
 x  3
 g   f  x  1
 2   2 x  1  3
x3
 1  2x  5
2
x5

2

22
c) f  g 1

## f  gx  f gx Let y = 2x + 1

 f  x  1 y 1
x
2
 2 x  1  3
x 1
 f  g x 
1
 2x  1 2

23
1 1
d) g  f
 x 3
g 1
f 1

x   g 
1

 2 
x3
 1
2
x 1

2

## Note that  f  g1 1

g f 1

24
Example 6

x p
Given the function f (x) = ,(x3),
x 3
where p is a constant. Find
a) The value of p if f ( 5 ) = 11
2
b) f -1

## c) the value of x for which f -1 is

undefined.

25
Solution :

a) 5 p 1
f (5)  
53 2 5 p 1
53 2

5+p = 3
p = -2

26
(b) From (a),

f(x)= y = x  2
x3
yx - 3y = x - 2
x( y -1) = 3y – 2
3y  2
Hence x =
y 1

-1
3x  2
Therefore, f (x) =
x 1
27
(c) f -1 is undefined for x =1
(This means that there is no value
of x in the original domain which

## So, 1 does not exist in the range

and therefore cannot be used.

28
THE GRAPH OF THE INVERSE

## The graph of an inverse function, f-1(x) of

the function f(x) can be obtained by
reflecting the graph f(x) about the line x= y.

Note :

Df = Rf-1
Rf = Df-1
29
Example 7 :
Sketch the graph of f and f-1 on the same axes.
Then find the domain and range of f and f-1 if
given f(x) = 3x + 2, x R

30
Solution :

## f(x) = 3x + 2, x R Df = ( -, + ) = Rf-1

x 2 Rf = ( -, + ) = D -1
f (x ) 
1
f
3

f y=x

2
f-1
2

31
Example 8 :

## For each of the function below, find the

inverse function and state the domain and
range of f-1. Sketch the graph of f and f-1
on the same axes.

a)f(x) = -x2 + 5, x  5
b) f (x)  x  2
2
c) f (x)  ,x  3
x 3
32
a) f(x) = -x2 + 5 , x  0

## The horizontal line

intersects
the graph at one point.

33
a) f(x) = -x2 + 5, x  5 Df = [ 0, + ) = Rf-1

## f 1(x)  5  x Rf = ( -, 5 ] = Df-1

y=x
5
f-1

5
f
34
b) h(x) = x  2 , x  2 Dh = [ 2, + ) = Rh-1
1 2 Rh = [ 0, + ) = Dh-1
h ( x)  x  2

h-1
y=x
2 h

35
2
c) f(x) = ,x>3
x 3 Df = ( 3, + ) = Rf-1
1 2  3x Rf = ( 0, + ) = Df-1
f (x ) 
x

f-1

y=x

f
3

36
Example 9 :
3
Find the inverse of f(x)= ( x + 4)(x – 1), x  
2
and stating its domain. Then, on the same
axes, sketch the graph of f and its inverse.

37
Solution :
3
y = ( x + 4)(x – 1) , x   By completing the
2
square
= x2 + 3x – 4
3 2 25
 (x  ) 
2 4
2
 3 25 1 3
 f (x )    x 
25
x    y  2 4
 2 4
3 25
x  y Taking positive
2 4 3
3 25 sign because x-
x  y 2
2 4 38
3 25
f (x )    x 
1

2 4
 25
D 1   , 
f
 4
f-1 y=x

25 3
 
4 2
3

2
25

4 39
Example 10 :

Given that f ( x ) = ( x – 9 )2 , x  R , x  9.
i) Find the inverse of function f .
ii) Sketch the graph of f and f -1 on
the same plane.
iii) State the domain and range of f-1.

40
a) To find f -1

## We may use f [ f -1(x) ] = x

( f -1(x) - 9 ) 2 = x
f -1(x) - 9 = x
( taking the + sign )

f -1(x) = x +9

Hence, f - 1 : x  x 9
41
b) Sketch the graphs
f
y y=k

f-1

x
9

c) Domain of f-1 : [ 0 ,  )
: [9,)
42
Range of f-1
Exercise :
1
Given that f (x) = 1 – x and g (x) = ,x  -2.
Find (f  g)1(x) x2

43